Multi-institutional evaluation of MVCT guided patient registration and dosimetric precision in total marrow irradiation: A global health initiative by the international consortium of total marrow irradiation. (December 2019) - Zuro, Darren; Vagge, Stefano; Broggi, Sara; Agostinelli, Stefano; Takahashi, Yutaka; Brooks, Jamison; Leszcynska, Paulina; Liu, An; Zucchetti, Claudio; Saldi, Simonetta; Han, Chunhui; Cattaneo, Mauro; et al.
Highlights: WBI institutions have lower overall setup error compared with PBI. MVCT WBI ensures accurate assessment of 3D regional and global dose variations. Variation is greatest in DVH of skeletal target at 90% and the lung at 10% isodose. Dose planning (avoidance vs targeting) has significant impact on lung dose coverage. Abstract: Purpose: Total marrow irradiation (TMI) is a highly conformal treatment of the human skeleton structure requiring a high degree of precision and accuracy for treatment delivery. Although many centers worldwide initiated clinical studies using TMI, currently there is no standard for pretreatment patient setup. To this end, the accuracy of different patient setups was measured using pretreatment imaging. Their impact on dose delivery was assessed for multiple institutions. Methods and materials: Whole body imaging (WBI) or partial body imaging (PBI) was performed using pretreatment megavoltage computed tomography (MVCT) in a helical Tomotherapy machine. Rigid registration of MVCT and planning kilovoltage computed tomography images were performed to measure setup error and its effect on dose distribution. The entire skeleton was considered the planning target volume (PTV) with five sub regions: head/neck (HN), spine, shoulder and clavicle (SC), and one avoidance structure, the lungs. Sixty-eight total patients (>300 images) across six institutions were analyzed. Results: Patient setup techniques differed between centers, creating variations in dose delivery. Registration accuracy varied by anatomical region and by imaging technique, with the lowest to the highest degree of pretreatment rigid shifts in the following order: spine, pelvis, HN, SC, and lungs. Mean fractional dose was affected in regions of high registration mismatch, in particular the lungs. Conclusions: MVCT imaging and whole body patient immobilization was essential for assessing treatment setup, allowing for the complete analysis of 3D dose distribution in the PTV and lungs (or avoidance structures).